Practical SQL queries for Microsoft SQL server 2008 R2 [ - Tennick, Art (McGraw-Hill, 2011)
"Learn powerful techniques for surfacing and delivering actionable business intelligence using SQL. Practical SQL Queries for Microsoft' SQL Server' 2008 R2 contains more than 400 downloadable SQL queries you can use to extract meaningful insights from large amounts of data. The application, syntax, and results of each query are described in detail. The book emphasizes SQL for use in SSMS, but the queries also apply to SSRS, SSIS, WinForms, WebForms, and many other applications"--Provided by publisher